Capacidad productiva de hongos lignocelulósicos (Pleurotus Ostreatus blanco y gris) en residuos de coco y cascarilla de arroz - Ortiz Basantes, Lady Mishel (2023)
Agro-industrial residues can be used efficiently for the benefit of food security, to achieve a profound transformation of food and agricultural systems around the world, in addition to being consistent with the change in the productive matrix of Ecuador. The purpose of this research project was to determine the productive capacity of lignocellulosic fungi (white and gray Pleurotus ostreatus) in coconut residues and rice husks and to analyze their bromatological characteristics (fiber, protein, fat), we worked with a Completely Aligned Design. Chance (DCA) with a 2x3 AxB bifactorial arrangement with 3 replicates for a total of 18 experimental units for solid medium fermentation. The study factors were made up of factor A = Pleurotus ostreatus fungi: (gray and white); B = Substrate: (coconut shell); (50% rice husk and 50% coconut shell); (rice husk extract), Completely Random Design (DCA) with a 2x4 AxB bifactorial arrangement with 3 repetitions for a total of 24 experimental units for culture media. as well as parameters were determined in the culture media (biomass production, mycelial growth rate) and in the fermentation of solid media (biological efficiency and yield) and proximal analyzes of fiber and protein were performed on the fungi. Keywords: Carpophore, Incubation, Substrates, Biological efficiency, Mycelium